Uji Aktivitas Ekstrak Etanol Daun Salam (Syzygium polyanthum) Terhadap Pertumbuhan Bakteri Methicilin-Resistant Staphylococcus aureus - Nuranti Rumela Sirait; Rosina Sitohang; Arman Bemby Sinaga; Maya Sari (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
Bay leaf (Syzygium polyanthum) is a family of Myrtaceae, which has been widely used as a spice in the kitchen, it turns out that it can be used as a traditional medicine to treat various diseases such as diabetes mellitus, hypertension, diarrhea, cholesterol, gastritis, and gout. Bay leaf (Syzygium polyanthum) can be used as a traditional medicine to maintain health and prevent various diseases because it contains alkaloid compounds, tannins, flavonoids, essential oils, and saponins. Methicillin-Resistant staphylococcus aureus (MRSA) is a cause of bacterial infections such as bacteremia, pneumonia, and surgical wound infections. Methicillin-Resistant Staphylococcus aureus can cause various complications, often in the bloodstream, joints, lungs, bones, and heart. This study was conducted with the aim of knowing the antibacterial activity of the ethanolic extract of bay leaves (Syzygium polyanthum) with concentrations of 5%, 10%, 15%, 20%, and 25% against the growth of Methicillin-Resistant staphylococcus aureus bacteria. This research method uses an experimental method, namely to determine the antibacterial activity of ethanol extract from bay leaves (Syzygium polyanthum) against the growth of Methicillin-Resistant staphylococcus aureus bacteria. This research used 96% ethanol as solvent. The test was carried out through several stages including material collection, preparation of Simplicia, manufacture of ethanol extract from bay leaves by maceration, and testing of antibacterial activity against Methicillin-Resistant staphylococcus aureus bacteria. Based on the results of phytochemical screening tests, the thick extract of bay leaf contains a class of alkaloids, flavonoids, glycosides, saponins, and tannins. The results of the antibacterial activity test of thick bay leaf extract against Methicillin-Resistant staphylococcus aureus bacteria had an average inhibitory activity at concentrations of 5% (6.55 mm), 10% (7.5 mm), 15% (8 mm), 20 % (8.8 mm) and 25% (11.06 mm).